Charge carrier self-organization in ferroelectromagnetic semiconductors Eu0.8Ce0.2Mn2O5 - Golovenchits, E.I.; Sanina, V.A.; Zalesskii, V.G.; Scheglov, M.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The state with a giant permittivity (ε΄ 104) and ferromagnetism has been observed above 185 K (including room temperature) in single crystals of diluted semiconductor manganite–ferroelectromagnetic Eu0.8Ce0.2Mn2O5 in the investigations of x-ray diffraction, dielectric and magnetic properties, conductivity. X-ray diffraction study has revealed a layered superstructure along the c axis at room temperature. A model of the state with a giant ε΄ including as-grown 2D layers with doping impurities, charge carriers, and double-exchange coupled Mn3+–Mn4+ ion pairs is suggested. At low temperatures these layers form isolated electrically neutral small-size 1D superlattices, in which de Haas van Alphen oscillations were observed. As temperature grows and hopping conductivity increases, the charge carrier self-organization in the crystal cause formation of a layered superstructure consisting of charged layers (with an excess Mn3+ concentration) alternating with dielectric layers of the initial crystal — the ferroelectricity state due to charge ordering. Ferromagnetism results from double exchange between Mn3+ and Mn4+ ions through of charge carriers in the charged layers.